Determinan saldo kas akhir tahun pada pemerintah daerah di Aceh - Syukriy Abdullah; Neza Muthia (Jurnal Akuntansi dan Auditing Indonesia, 2017)
This research examines the effect of the government size, rebudgeting, previous year cash balance, and budget absorption on end-year cash balance of local governments in Aceh for 2013-2015 periods. Secondary data were extracted from local government’s budget documents and financial statements by using 23 regencies and cities as samples. This research used multiple linear regression to test the hypothesis and found that the end-year cash balance is (1) positively affected by government size and previous year cash balances; (2) not affected by rebudgeting, and (3) negatively affected by budget absorption.